Dynamic morphological examination and evaluation of biological characteristics of a multinodular liver cancer model in mice. (April 2014) - Li, Yan-Ru; Wang, Jin-Rui; Zhang, Hai-Ying; Wu, Xiao-Fei; Li, Sheng-Nan; Wang, Lin; Wang, Xue-Yao
Compared with single nodular liver cancer, the prominent biological characteristics of multinodular liver cancer include rapid progression and short survival. Here, we developed a multinodular liver cancer model in mice and assessed the biological characteristics of the resulting neoplasms. H22 hepatoma cells at a dose of 2 × 10 5 /mouse, suspended in 1.6 mL, 0.8 mL, or 200 µL saline were injected via the tail vein of BALB/c mice at a velocity of 200 µL per second. The mice were sacrificed at different time points after injection. And at the time of death the liver, lungs, spleen, kidneys and heart were removed for morphological study. The biological characteristics of the tumor nodules were evaluated by immunohistochemistry. In the mice treated with a large volume injection of H22 cells, by day 7, there was a 100% occurrence of multinodular tumors in the livers, determined by histology. At the time of death, there were 100%, 100%, 37.5% and 37.5% occurrences of tumors in the lungs, kidneys, spleen and heart, respectively. The neoplastic cells in the liver nodules showed pleomorphism, and exhibited high expression of proliferating cell nuclear antigen (PCNA), c-myc, vascular endothelial growth factor (VEGF) and matrix metalloproteinase 2 (MMP-2). In mice treated with a small or medium volume injection, no tumor cells were identified in the livers, spleen, kidneys or heart at any of the examined time points. By day 7 and at the time of death, there was a 100% occurrence of tumor in the lungs. A multinodular liver cancer model in mice was achieved using a large volume injection of H22 cells.